The development of immunolabelling techniques for the investigation of testosterone levels in the Leydig cells of the cryptorchid testis - Aggenbach, Celia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Med. Sc.) -- University of Stellenbosch, 1987.